How Mindfulness Affects Life Satisfaction: Based on the Mindfulness-to-Meaning Theory - Li, Xiaojun; Ma, Liping; Li, Qi (Frontiers in Psychology, 2022)
Life satisfaction is the general evaluation of the individual’s life, which is of great significance to achieving a better life. The purpose of the present study was to investigate the mediating effect of core self-evaluation, positive affect, and negative affect in the relationship between trait mindfulness and life satisfaction based on the Mindfulness-to-Meaning theory. 991 Chinese undergraduates (692 females, 299 males) completed the Mindful Attention Awareness Scale, the Core Self-Evaluations Scale, the Positive Affect and Negative Affect Scale, and the Satisfaction with Life Scale. The results indicated that core self-evaluation and negative affect mediated the effect of trait mindfulness on life satisfaction, consistent with the Mindfulness-to-Meaning theory. Furthermore, trait mindfulness affected life satisfaction by the mediation paths of "core self-evaluation→positive affect" and "core self-evaluation→negative affect," which uncovered the underlying mechanism of promoting life satisfaction by combining the point of view of cognition (core self-evaluation) and emotion (positive and negative affect). The present study not only contributes to a better theoretical understanding of how trait mindfulness links to life satisfaction but also provides valuable guidance for enhancing life satisfaction.